Health Economics of Genetic Distance - Pavel Jelnov (Global Labor Organization (GLO), 2020)
In this note, I address the trade-off between children's health and parental preference toward similarity with children. In my model, better-off individuals mate genetically close partners and then use wealth to treat their children's health problems, caused by inbreeding depression. As a result, the relationship between parental wealth and children's health includes decreasing portions. Siblings health inequality is also nonmonotonically related to parental wealth, if parents discriminate in favor of more similar children.
Keywords: J12; J13; N30; 330; inbreeding; genetic distance; health inequality